The strategy of tourism products complementarity in destination promotion: Eurocity Chaves-Verín - Liberato, Dália (2022)
The process of tourism destination governance should result from the link between local authorities, communities, and the business sector, aiming at the sustainable development of the region on the economic, environmental, and social levels. Another essential factor is the complementarity of tourism products, especially when combined with an innovation factor. The Bio-Healthy Plans aim to ensure complementarity in the supply of all the region's resources: mineral-medicinal water, gastronomy, wines, nature, culture, health and well-being, as an innovative product, fostering the “rediscovery” of natural mineral water consumption as part of healthy diets and programs. Tourism governance also has a fundamental role, by preserving local identity and interests in a sustainable way, since sustainability is the basis for the local development of a territory. The main objective of this article is to understand the tourism potential of the border destination Eurocity Chaves-Verín as a health and wellness destination and the importance of the tourism offer complementarity visioning the sustainable governance of a tourism destination. A qualitative methodology was used, by conducting interviews with public and private entities. The literature review discussed concepts of tourism governance, the complementarity of tourism products, tourism and health and wellness activities, and bio-healthy plans. The results show that the thermal offer, despite being perceived as unique in the destination, is not mentioned as the main purpose of the visit in the Destination Tourism Monitoring study. The goal of promoting the destination with the integration of all tourism products offered in the region is consensual. Additionally, the importance of involving all stakeholders in the strategic planning, the destination promotion, and the design of innovative tourism products is recognized.